Studies on the Effect of Diamine Elongation in Copper(II) Complexes with NNO Tridentate Schiff Base Ligands - Chiara Canovi; Francesco Genua; Kevin D’Addazio; Lara Gigli; Alessandra Forni; Petr Michálek; Mauro Carcelli; Dominga Rogolino; Luca Rigamonti (Inorganics)
The copper(II) complexes of general formula [Cu(GL2H,H)(Cl)] (A4–A6, G = NO2, H and OMe, respectively), bearing NNO tridentate Schiff base ligands (GL2H,H)− derived from the mono-condensation of 1,3-diaminopropane and G-substituted salicylaldehydes, are here reported. The elongation of the diamine with one additional carbon atom with respect to the triad derived from ethylenediamine [Cu(GL1H,H)(Cl)] (A1–A3, G = NO2, H and OMe, respectively) led to different synthetic procedures, with the difficult isolation of A6 that could be obtained only in few crystals suitable for X-ray diffractions. Operating in acidic conditions to promote the coordination of chloride and expulsion of pyridine from the complex [Cu(GL2H,H)(py)](ClO4) (G = NO2) allows for obtaining A4. On the other hand, structural rearrangement occurs when G = H, yielding the dinuclear species [Cu2(μ-saltn)(HL2H,H)](ClO4)⋅0.5MeOH (D5⋅0.5MeOH) instead of the desired A5, which can be obtained by avoiding the use of HCl and operating in the excess of LiCl. Finally, A4 and A5 were investigated as cytotoxic agents against malignant (MDA-MB-231 and 22-Rv1) and healthy (HaCaT) cell lines, and the ability of the most promising A5 to be internalized and interact with cellular targets was studied.